Pengaruh Pelatihan dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan pada Perumda Air Minum Tirta Sukapura Kabupaten Tasikmalaya - Desti Rosmiatun Barnas; Adi Muhammad Nur Ihsan (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
This study aims to test and analyze the effect of training and extrinsic motivation on employee performance at Perumda Air Minum Tirta Sukapura, Tasikmalaya Regency. The research method applied is a quantitative verification approach, with data collection techniques using a Likert-based questionnaire distributed to employees. The data obtained were then processed using SPSS software version 26. The results of the analysis show that training has a positive and significant effect on employee performance (sig. 0.011 < 0.05). A positive and significant impact is also shown by extrinsic motivation (sig. 0.006 < 0.05), which is also a variable with a more dominant influence than training. Furthermore, the results of the determination coefficient test (R2) of 0.508 indicate that the contribution of training and extrinsic motivation in explaining employee performance is 50.8%, while the remaining 49.2% is explained by other factors outside this research model. Based on these findings, Perumda Air Minum Tirta Sukapura, Tasikmalaya Regency, is advised to optimize the performance of its employees by increasing extrinsic motivation and the quality of training supported by providing awards, appropriate incentives, leadership support, and a positive work environment.